Eliciting time preferences when income and consumption vary: Theory, validation & application to job search - Michele Belot; Philipp Kircher; Paul Muller (Tinbergen Institute, 2021)
We propose a simple method for eliciting individual time preferences without estimating utility functions even in settings where background consumption changes over time. It relies on lottery tickets with high rewards. In a standard intertemporal choice model high rewards decouple lottery choices from variation in background consumption. We validate our elicitation method experimentally on two student samples: one asked in December when their current budget is reduced by extraordinary expenditures for Christmas gifts; the other asked in February when no such extra constraints exist. We illustrate an application of our method with unemployed job seekers which naturally have income/consumption variation.
Keywords: J64; D90; 330; time preferences; experimental elicitation; job search; hyperbolic discounting